2017
DOI: 10.5812/ajcmi.12105
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Antibiotic Resistance with Spa Gene Polymorphism Coding Protein A and its Typing with PCR-RFLP Technique in S. aureus Isolated from Foodstuffs

Abstract: Background: Staphylococcus aureus is an important cause of hospital and community acquired infections. Food borne diseases are an important problem in public health. Protein A is a protein 42 KDa, which is expressed in all strains of this bacterium. Objectives: This study aimed to evaluate the relationship between antibiotic resistances with spa gene polymorphism. Methods: A total of 1,050 food samples were collected during 8 months in Hamedan, Iran. Food samples were evaluated for the presence of spa genes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The occurrence and the type of antibiotic resistance strongly correlated with the spa- type. Recently, this has also been reported between clindamycin and erythromycin resistances and the spa -type; although there were no correlations between the occurrences of cefoxitin, gentamicin, tetracycline, and trimethoprim/sulfamethoxazole resistances ( 35 ). However, in this study the spa -types have been identified by PCR and not by sequencing.…”
Section: Discussionmentioning
confidence: 94%
“…The occurrence and the type of antibiotic resistance strongly correlated with the spa- type. Recently, this has also been reported between clindamycin and erythromycin resistances and the spa -type; although there were no correlations between the occurrences of cefoxitin, gentamicin, tetracycline, and trimethoprim/sulfamethoxazole resistances ( 35 ). However, in this study the spa -types have been identified by PCR and not by sequencing.…”
Section: Discussionmentioning
confidence: 94%
“…Staphylococcus aureus is clearly known to be a potential pathogen that causes many infections (Hosseini et al, 2017). These infections are classified into three types of skin infections and various toxicities such as food poisoning, septic shock, toxic shock syndrome and scaled skin syndrome (Freeman-Cook et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…0.5 McFarland suspension of Brucella melitensis were cultured on Mueller-Hinton agar plates using sterile swabs. In the following step, Wells 8 mm in size were created in culture media by using a sterile Pasteur pipette and each well was filled in by 100 μl of nanodrugs and free drug and incubated at 37°C for 24, 48, and 72 h. After these time intervals, bacterial growth around the wells was measured for each well and used as a basis for analyzing the antibacterial performance of nanodrugs ( Hosseini et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%